Life-Cycle CO2-Equivalent Emissions of Cars Driven by Conventional and Electric Propulsion Systems - Mario Hirz (World Electric Vehicle Journal, 2022)
As an important trend in the automotive industry, electrification of propulsion systems has potential to significantly reduce greenhouse-gas emissions of the transportation sector. Whereas electric vehicles do not produce exhaust emissions during driving, the impact of electricity provision for charging batteries, as well as the impact of vehicle production play an essential role in a holistic consideration of the carbon footprint. The paper introduces a comprehensive evaluation of greenhouse gas-emission-related factors of cars driven by different propulsion technologies, considering the entire product life cycle. This comprises vehicle production, including battery system, electric powertrain and other relevant components, the car’s use phase under consideration of different electricity mixes and the end-of-life phase. The results of the study give insights of influencing factors on life-cycle-related carbon-dioxide-equivalent emissions of cars driven by combustion engines, hybrid powertrains and battery-electric propulsion systems. In addition, a comparison of actual mass-production cars is made and the total life-cycle carbon footprints are discussed under different boundary conditions of electric power supply. In this way, the article comprehensively introduces an automotive life-cycle assessment and provides fundamental information, contributing to an objective discussion of different propulsion technologies.